Ad Hoc percutaneous coronary intervention: A consensus statement from the society for cardiovascular angiography and interventions. Issue 5 (29th November 2012) - Blankenship, James C.; Gigliotti, Osvaldo S.; Feldman, Dmitriy N.; Mixon, Timothy A.; Patel, Rajan A.G.; Sorajja, Paul; Yakubov, Steven J.; Chambers, Charles E.
<x xml:space="preserve">Abstract</x> Percutaneous coronary interventions (PCI) may be performed during the same session as diagnostic catheterization (ad hoc PCI) or at a later session (delayed PCI). Randomized trials comparing these strategies have not been performed; cohort studies have not identified consistent differences in safety or efficacy between the two strategies. Ad hoc PCI has increased in prevalence over the past decade and is the default strategy for treating acute coronary syndromes. However, questions about its appropriateness for some patients with stable symptoms have been raised by the results of recent large trials comparing PCI to medical therapy or bypass surgery. Ad hoc PCI for stable ischemic heart disease requires preprocedural planning, and reassessment after diagnostic angiography must be performed to ensure its appropriateness. Patients may prefer ad hoc PCI because it is convenient. Payers may prefer ad hoc PCI because it is cost‐efficient. The majority of data confirm equivalent outcomes in ad hoc versus delayed PCI. However, there are some situations in which delayed PCI may be safer or yield better outcomes. This document reviews patient subsets and clinical situations in which one strategy is preferable over the other. © 2012 Wiley Periodicals, Inc.